EDUKASI SADAR (SEMANGAT MENGATASI DAN DETEKSI RESIKO) DALAM MEMBANGUN MASYARAKAT SAYANG GINJAL - Kheniva Diah Anggita; Anisa Fadilah; Rifqi Aulia Zaim; Prima Yoselina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Sikapak Barat village, located in the North Pariaman sub-district, has the highest number of hypertension and diabetes mellitus cases among the six villages served by the Sikapak Public Health Center. The majority of its residents are farmers and laborers with demanding routines, who often rely on packaged and canned energy drinks to combat fatigue. While these beverages are seen as a way to stay refreshed and boost energy, excessive long-term consumption can lead to various negative health consequences, including kidney disease. This community service project provides an alternative strategy to control the risk factors for kidney disease. This involves conducting blood pressure and blood sugar screenings and providing support on overcoming and detecting risks education using a Focus Group Discussion (FGD) method, to foster a